IMPROVEMENT OF FINANCIAL CONTROL OF ECONOMIC ENTITIES AND THEIR MANAGEMENT SYSTEM (World Economics and Finance Bulletin, 2025)
This article extensively covers the issues of financial control of business entities and improving their management system. Also, the need for financial control of enterprises is scientifically substantiated. In addition, models for radically improving the financial control of business entities and their management system are analyzed. In addition, conclusions and proposals are developed on improving the financial control of business entities and their management system.